INSTITUTIONAL AND FUNCTIONAL FRAMEWORKS FOR CAPITAL MARKETS IN THE REPUBLIC OF SERBIA - Simić, Nataša; Bozilovic Djokic, Dragana; Djokic, Vladimir (Journal of process management and new technologies, 2021)
Globalization of financial flows, monetary integration, deregulation and cutting-edge information technology promote the growth of efficient capital market, as an integral part of national financial markets. The aim of this paper is to point out advantages and disadvantages of the development of relatively new capital market in the transition period of the Serbian economy. In the broadest sense, financial market is an organized place, where supply and demand for financial asset meet, forming the price of financial asset. In short, financial market includes all the institutions and procedures by which sellers and buyers of financial instruments are connected regardless of the nature of financial instrument. It enables unhindered funds and capital flow to the place where it can be employed most efficiently. Financial market development, depth and stability are crucial for economic growth and they are also a significant indicator of national market development in relation to its environment.
Keywords: market; capital; transition; globalization; financial instruments